(untitled) (Research, Society and Development, 2023)
Acute discomfort syndrome (ARDS) is the most common cause of voice discomfort in newborns (NBs). Being responsible for the deaths of several people in this population. In this sense, the objective of this study was to analyze the number of deaths in newborns between the years 2010 to 2020. The present study is an epidemiological study developed through the collection of secondary data in the DATASUS information system. The following variables were considered for the study: region, age of the NB, type of delivery, type of pregnancy and length of pregnancy. Descriptive analyses were performed using the SPSS version 22.0 tool (IBM SPSS Corp., Armonk, NY). For data summarization, means, standard deviation, absolute and relative frequency were shown. The results reached a higher prevalence of deaths in the Southeast region, in male NBs, aged less than 6 days, born by vaginal delivery, single pregnancy and gestation period between 22 and 27 weeks. In general, these data suggest that some variables may be related to the death of individuals. In addition, studies also prove that physiotherapy through its respiratory techniques can be important for the reduction of death complications in these NBs.